Terjebak di Dunia Maya: Peran Kontrol diri dan Keberfungsian Keluarga Terhadap Problematic Internet Use pada Remaja Akhir di Kabupaten Karawang - Bayu Setiawansyah; Dinda Aisha; Ananda Saadatul Maulidia (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
One of the problems faced by late adolescents is excessive and uncontrolled internet use which has the potential to cause Problematic Internet Use (PIU) which will impact daily life activities. This study aims to determine the effect of self-control and family functioning on PIU in late adolescents in Karawang Regency. The researcher used a quantitative approach that emphasizes numerical data analysis through statistical techniques. Respondents in this study numbered 400 late adolescents aged 17-21 years who were selected using non-probability sampling with convenience sampling technique. The instruments in this study were measured using three scales: the Brief Self-Control Scale (BSCS), the Family Assessment Device-General Functioning (FAD-GF), and the Problematic Internet Use Questionnaire-Revised (PIUQ-R). Data analysis used multiple regression tests using SPSS version 25.0 for Windows. The results of this study indicate that self-control and family functioning partially and simultaneously influence PIU. The regression coefficient is negative, meaning that the higher the self-control and family functioning, the lower the PIU. Self-control and family functioning contributed 51.7% to PIU. Therefore, improving individual self-control and optimizing family functioning could be potential efforts to minimize PIU in late adolescence, particularly in the context of this study's target group.